Studi Eksperimental Karakteristik Capillary Rise Material Karbon Aktif Bambu Betung Dengan Holding Time 30 Menit Sebagai Material Pad Alternatif - Surya Pranata, Gede Ngurah; Wijaksana, Hendra; Putu Tenaya, I Gusti Ngurah (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstract Evaporative Cooler is a cooling machine that uses the principle of evaporative cooling. Evaporative cooling is technically called adiabatic cooling which is an air conditioning process that is carried out by allowing direct contact between air and water vapor so that there is a change from sensible heat to latent heat. The main component of the evaporative cooling system is the pad material. Capillary rise of a porous material can be indicated by its capillary rise, where capillary rise is the rise of the liquid surface above atmospheric pressure due to an upward force on the material produced by the attractive forces between the liquid molecules and the solid surface molecules material (adhesion force). The purpose of this study was to analyze the characteristics of the capillary rise pad material based on bamboo betung activated carbon with a holding time of 30 minutes. In this study, several stages of testing were carried out, namely the bamboo drying process, carbonization and activation, and SEM testing. The basic material of bamboo betung will be carbonized with carbonization temperatures of 400oC, 500oC, 600oC, 700oC and 800oC, before finally being activated at an activation temperature of 600oC with a holding time of 30 minutes which aims to open the smaller bamboo pores. With these two thermal treatments, it is expected to increase the pore structure and porosity of the bamboo betung so that it can produce a high capillary rise to lift more mass of water into the bamboo betung activated carbon material. Furthermore, the SEM (Scanning Electron Microscopy) test was carried out to obtain the characteristics of the pore structure of the sample. The results of this study indicate that the largest capillary rise is produced by the active carbon material of bamboo betung ACR (carbonization activation) 700 while the lowest capillary rise is produced by the activated carbon material of bamboo betung ACR (carbonization activation) 600. Keywords: Capillary Rise, Bamboo Betung, Holding Time 30 Minutes